LARGE DEFLECTION ANALYSIS OF ANISOTROPIC LAMINATED PLATES BY CONTINUOUS AND NON-CONTINUOUS GFEM (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This work addresses the application of the GFEM to laminated plates under moderately large transverse displacements by the von K´arm´an’s hypothesis, in the frame of the Kirchhoff-Love and Reissner-Mindlin kinematical plate models. The formulation admits the general case of laminated plates composed of anisotropic layers in the elastic range. The behaviors of two types of GFEM formulations are compared, one based on C0 continuous Partition of Unity (PoU), and the other is based on continuous PoU. The adequate number of integration points in the element is investigated for each degree of enrichment polynomial. For the transverse shear stresses obtained from integration of the local equilibrium equations, a theorem is presented to explain the reason why, in some cases, the null value is not reached at the end of the integration across the laminate thickness. Numerical results are compared with literature.